Problems in gynaecologic oncology in girls and young women-an outline of selected issues - Katarzyna Plagens-Rotman; Maria Połocka-Molińska; Piotr Merks; Matylda Gwoździcka-Piotrowska; Witold Kędzia; Grażyna Jarząbek-Bielecka (IMR Press, 2021)
Objective: The aim of the study was to present selected oncological problems among girls and young women. Mechanism: Malignant ovarian cancers grow faster in girls. Due to the lack of an anatomic barrier, they spread rapidly from the pelvis to the organs in the entire peritoneal cavity. High-grade cancers may be associated with an insufficient immune response that controls the early tumour growth. Findings and brief: Paediatric cancers represent about 1% of all diseases; fortunately, in developmental age gynaecology this is not a frequent problem, yet its significance requires intense specialist actions. Although they most often occur in adult women, malignant lesions may also affect girls (e.g., cervical germ cell tumour). Therefore, the importance of early detection of neoplastic ovarian lesions at any age is emphasised. Cervical cancer is also an oncological issue in developmental age gynaecology (the immature metaplastic epithelium is particularly sensitive to the oncogenic effects of HPV (Human Papillomavirus)), hence any prophylaxis, especially vaccinations, are of great importance in this respect). Apart from typical genital cancers, there can also be cancers where the genitourinary system is just one of the possible locations. Conclusions: Fortunately, cancers are not frequent in developmental age gynaecology, yet the significance of this problem requires intense specialist actions.